2014
DOI: 10.1590/1516-3180.2014.1323653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating psychiatric case-control studies using the STROBE (STrengthening the Reporting of OBservational Studies in Epidemiology) statement

Abstract: CONTEXT AND OBJECTIVE: Case-control studies are important in developing clinical and public health knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…The evaluated articles in our study, similar to the ones in other studies (2,6,14,15) had reported averagely half of the items recommended by the statement. This highlighted a clear need to improve the quality of the reporting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The evaluated articles in our study, similar to the ones in other studies (2,6,14,15) had reported averagely half of the items recommended by the statement. This highlighted a clear need to improve the quality of the reporting.…”
Section: Discussionsupporting
confidence: 86%
“…Up to now, several studies evaluated the adherence of different kinds of observational studies, case-control ( 6 ), cross-sectional ( 7 ), and cohort ( 8 ), to the STROBE statement. The studies published in a specific journal ( 9 ) or presented in a congress ( 10 ) were also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…This shows how necessary it is for the researcher to choose a methodological design befitting the proposed objective while considering the existence of possible biases and the methods of controlling them, and present this information for the reader. 17,18 minimizing memory bias in case-control studies is to use data that was collected in a systematic way before the development of the disease; for example, organized and complete medical records could be used.…”
Section: Information Biasmentioning
confidence: 99%
“…Le « STROBE Statement » est particulièrement utilisé par les profession nels de la réadaptation, 2 mais est également employé par d'autres professionnels de la santé. [3][4][5][6][7][8] Afin de vérifier si les conclusions des EO sont solides, le clinicien averti doit s'assurer de la présence de tous les éléments méthodologiques caractéristiques rapportés dans les écrits scientifiques. 9 Il existe des instruments de mesure validés en français pour examiner la présence d'éléments méthodologiques caractéristiques des essais cliniques randomisés, 10 des revues systématiques, 9 pour les « lignes directrices cliniques ».…”
unclassified